MINAT BRAIN GAIN MAHASISWA RANTAU ASAL SUMATERA DI FAKULTAS-FAKULTAS AGROKOMPLEKS UNIVERSITAS PADJADJARAN - Elfa Dela Rahmanisa; Iwan Setiawan (Universitas Galuh Ciamis, 2020)
Youth interest in becoming young agribusiness actors tends to below, however, it needs further study especially for students in the Unpad agro complex faculty. Interest is a feeling in someone to follow activity as a basis for a job. Four factors affect student interest, namely: (1) encouragement in individuals; (2) social motives; (3) emotional factors; and (4) economic motives. This study aims to explain the interest in the brain gain of agro complex migration students and to analyze the factors that influence the brain gain interest. This research is quantitative research with a survey method. The analysis used is multiple linear regression test. The results showed that interest in brain gain in overseas students was classified as high at the interest stage. Based on the t-test, the factors that influence the interest of active students from Sumatra in Unpad agro complex faculties are encouragement factors in individuals.